2000
DOI: 10.1098/rstb.2000.0708
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite–dependent nitric oxide production pathway: implications for involvement of active nitrogen species in photoinhibitionin vivo

Abstract: Air pollution studies have shown that nitric oxide (NO), a gaseous free radical, is a potent photosynthetic inhibitor that reduces CO 2 uptake activity in leaves. It is now recognized that NO is not only an air pollutant but also an endogenously produced metabolite, which may play a role in regulating plant cell functions. Although many studies have suggested the presence of mammalian-type NO synthase (NOS) in plants, the source of NO is still not clear. There has been a number of studies indicating that plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
150
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(163 citation statements)
references
References 112 publications
4
150
0
1
Order By: Relevance
“…The results can be summarized as follows: (i) Nitrate and nitrite are the main nitrogen sources for the basal level of NO production in leaves of V. faba, A. thaliana, and H. rosa sinensis. This finding is consistent with the view that nitrite reduction by NR is responsible for NO generation in leaves (1,7,9,18,20,21,42). (ii) Superoxide anion production interferes with the detection of endogenous NO.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The results can be summarized as follows: (i) Nitrate and nitrite are the main nitrogen sources for the basal level of NO production in leaves of V. faba, A. thaliana, and H. rosa sinensis. This finding is consistent with the view that nitrite reduction by NR is responsible for NO generation in leaves (1,7,9,18,20,21,42). (ii) Superoxide anion production interferes with the detection of endogenous NO.…”
Section: Discussionsupporting
confidence: 81%
“…This result favors the idea that NR is a significant source of NO production in plant leaves under basal conditions. We suggest that, in agreement with other studies (18,20), nitrate added at high millimolar concentrations inhibits the nitrite reductase activity of the enzyme by a competitive mechanism, thereby attenuating NO production in the leaves.…”
Section: Isolated Leaves From Beans and A Thaliana Can Spontaneouslysupporting
confidence: 76%
See 1 more Smart Citation
“…NO 3 Ϫ is a competitive inhibitor of NO production in leaves, and NO production was dependent on a number of factors, including cytosolic NO 3 Ϫ and NO 2 Ϫ concentrations, light, oxygen availability, and serine phosphorylation of nitrate reductase (47). The role of NO production by plants has been widely discussed, and it is possible that low level NO production by nitrate reductase may have a role in cellular signaling, in particular in establishing symbiosis and in defense against pathogens (62). However, in planta, mutant studies have shown that NO 2 Ϫ may be the major source of NO by Arabidopsis thaliana, when the plant is challenged with infection (61).…”
Section: Discussionmentioning
confidence: 99%
“…Plant nitrate reductase is now well established as producing NO (45,47,(61)(62)(63). Purified cytosolic nitrate reductase produces NO with NADH as the electron donor (45) and, like the work presented here, the reaction is azide-sensitive (63).…”
Section: Discussionmentioning
confidence: 99%